Analisis Kondisi Fisik Pemain Tim Kresna Unesa FC Dalam Mengarungi Kompetisi Liga 3 Jawa Timur Tahun 2023 - Rizky Iswantur Rahman; Mokhamad Nur Bawono; Indra Himawan Susanto; Soni Sulistyarto (LPPM Politeknik Pratama, 2024)
This study aims to analyze the physical condition of football players from various aspects including strength, endurance, speed, flexibility, and agility. This research is descriptive in nature with a quantitative approach. The population and sample in this study are the 20 players of Kresna Unesa FC using total sampling technique. The data used are primary and secondary data. Data collection methods include observation, literature review, and direct measurement tests involving amateur football players competing at the national level. The data analysis technique used is descriptive analysis with percentage point calculations for the physical condition categories of football players with value conversion used for analysis. The results of this study show that the physical condition of the players of the Kresna Unesa FC team during the 2023 East Java Liga 3 competition in each test item are as follows: in the first test of 30-meter sprint, 45% of players have good speed and 55% have average speed. The second test of endurance shows that 5% of players have very good endurance, 30% have good endurance, 60% have average endurance, and 1% have poor endurance. The flexibility test shows that 100% of players have good flexibility. In the fourth test of lower limb muscle power, 5% of players are in the good category, 45% are in the average category, 45% are in the poor category, and 5% are in the very poor category. The agility test shows that 35% of players are in the good category, 45% are in the average category, and 20% are in the poor category. The sit-up test shows that 5% of players are in the poor category and 95% are in the very poor category. The push-up test shows that 20% of players are in the good category, 15% are in the average category, 40% are in the poor category, and 25% are in the very poor category. This study highlights the importance of proper physical conditioning in football players to enhance their performance on the field. The practical implications of this research can assist coaches and fitness staff in designing training programs tailored to the individual needs and positions of players.